Quality Assessment of Educational Services in the College of Education, University of Dammam, Using (SERVQUAL) Scale - Khalid H. Al-shughibi; Mohammed S. Al-mekhlafie (Sultan Qaboos University, 2016)
The study aimed at measuring educational services quality at the College of Education in Damam as perceived by students. For this purpose a sample of 286 students was selected randomly. The findings revealed overall negative statistical significant gap between students perception and expectation and the different service levels/dimensions. The study also showed negative statistical significant gap attributed to gender in their overall perceptions towards the areas: reliability, responsiveness, safety, empathy, in favor of males. The study also showed no significant differences attributed to gender in the students overall expectation of the educational services and in the areas reliability, responsiveness, safety and empathy. In addition, there were significant differences among the students expectations of the services in overall the moral aspects in favor of those enrolled at the post B. Ed program and no significant differences among them in the degree of importance in the tangible aspects such as responsiveness and empathy attributed to their educational level; whereas there were significant differences in the overall and in the moral aspects between the views of the expected and the perceived services in the overall and the areas tangible aspects, reliability, responsiveness, safety and empathy, in favor of the expected services.